Social Safety Nets for Labor Welfare and their Extent of Coverage in Khyber Pakhtunkhwa, Pakistan (Journal of Social Sciences Review, 2025)
This study has been carried out with the purpose to introduce the readers with the services and facilities being provided by the government of Khyber Pakhtunkhwa to workers who are working in different small and medium industries in District Peshawar. Labor force is regarded to be the backbone of any industrial society. In Pakistan, laborers are facing multitude of problems, however, the state is committed to provide the industrial workers with different services and facilities. In order to cope with risks and unseen contingencies each province in Pakistan has established social safety nets for their industrial workers. These includes the employees’ social security institution, employees’ old age benefits institution, and workers’ welfare board. These social safety nets provides laborers with different services and facilities i.e. educational stipend to children of the workers, disability allowance, sickness benefits, health services, survivors’ pension, jahaiz fund, care for workers’ dependents, and death grants etc. This study has evaluated the nature and extent of the social safety nets in Khyber Pakhtunkhwa. The study suggests that all the industrial workers should be provided with all social security services.
Keywords: Social Safety Nets; Employees’ Social Security Institutions; Employees’ Old Age Benefits Institutions; Worker Welfare Board; Industrial Workers